Homo-Chromophores in Cu(I)(XXX), (X3 = N3, C3, Cl3, S3, P3, Br3, or I3) Derivatives—Structural Aspects - Milan Melník; Veronika Mikušová; Peter Mikuš (Inorganics)
The structural aspects of homo-chromophores in Cu(I)(XXX) complexes, where X3 = N3, C3, Cl3, S3, P3, Br3, or I3, are analyzed in this study. These copper(I) derivatives crystallize in five distinct crystal systems as follows: rhombohedral (1 example), trigonal (1 example), orthorhombic (4 examples), triclinic (5 examples), and monoclinic (15 examples). The angular distortion from regular trigonal geometry increases in the following order: Cu(ClClCl) < Cu(NNN) < Cu(PPP) < Cu(BrBrBr) < Cu(III) < Cu(CCC) < Cu(SSS). For Cu(I)(XX) complexes, the deviation from linear geometry increases in the order: Cu(SeSe) < Cu(SS) < Cu(OO) < Cu(ClCl) < Cu(NN) < Cu(CC) < Cu(PP) < Cu(BrBr). The structural parameters of Cu(I)(XXX) are examined, discussed, and compared with those of homonuclear Cu(I)(XX) complexes.